Comercio exterior - Martínez, Marco (1997)
This article was scanned by the Aurelio Espinoza Polit Ecuadorian Library. The process of globalization of the world economy determined an irreversible path for the Ecuadorian The globalization process of the world economy determined an irreversible path in the Ecuadorian productive structure that placed it directly in competition in the market of goods and services at the international level. Unfortunately for Ecuador, the conditions in which we enter this competition are very unequal, due to our lack of availability of economic resources and technology, which is even worse if we consider that "We enter to compete in markets already dominated by developed economies and, therefore, that are in better conditions than us in structure and experience on international trade relations.